Pengaruh Manajemen Rantai Pasokan terhadap Kinerja Perusahaan Kosmetik menggunakan Structural Equation Model – Partial Least Square - Anita Anita; Nuril Izzy Sabila (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Significant changes have occurred in the economy, especially in developing countries such as Indonesia, where the economic, development and industrial sectors continue to improve. Manufacturing companies in the cosmetics subsector are an industry that has quite intense competition in Indonesia. According to the first quarter of 2020 data from the Central Bureau of Statistics, the market growth of this industry averaged 5.59% per year. This is expected to continue in the coming year. The implementation of supply chain management (SCM) will support organizations to have a good performance system. PT Zoey Cosmedica Putra (Maklon Kosmetik) is one of the manufacturing companies engaged in the cosmetics industry. The purpose of this study is to analyze the effect of supply chain management on company performance. Data processing using the Structural Equation Modeling - Partial Least Square (SEM-PLS) method using Smart PLS software version 4.0. The results of SCM factor analysis research measured by independent variables, namely relationships with suppliers (X1), relationships with customers (X2) and the level of information sharing (X3) with the dependent variable, namely company performance (Y). Shows X1 and X3 hypotheses have an influence, while the X2 hypothesis has no effect.